Realitas Sosial Masyarakat Palestina dalam Film Inch'Allah: Semiotika Charles Sanders Peirce - Royyi Muwaffa (Universitas Negeri Jakarta, 2021)
The film Inch’Allah depicts the life of the Palestinian people due to the war with Israel. The scenes in this film are filled with codes that aim to attract sympathy and empathy from other countries. The problem in this research is the use of signs used by Anaïs Barbeau-Lavalette in describing the life of the Palestinian people and the actions of the Israeli soldiers depicted through these signs. This study aims to uncover the forms of signs and their relationship to objects contained in these signs. The method used is a qualitative method with an objective approach. The theory used is the semiotic theory of Charles Sanders Peirce. In this study, the researcher found ten scenes describing Israeli soldiers' attitudes and actions between the two countries. The social representation depicted in the film is the poverty faced by the Palestinian people. All of their possessions had been lost along with the pieces of their house. There is no longer any freedom for the Palestinian people to do anything.